Complementary effect of crop wastes and inorganic fertilizers on yield, nutrient uptake and residual fertility in mustard (Brassica juncea) - rice (Oryza sativa) cropping sequence - KUMAR, VINOD; GHOSH, B C; BHAT, RAVI (The Indian Journal of Agricultural Sciences, 2013)
A field experiment was,conducted during 1992-93 and 1993-94 to study the direct and residual.l effects of different organic and inorganic sources of fertilizers in the mustard [Brassica juncea (L.) Czernj. & Cosson]-rice (Oryza sativa L.) cropping sequence in acid lateritic sandy clay loam soil at Kharagpur. There was an increase in mustard yield by about 165% with higher level (N60 P36 K24) offertilizer application. But there was no significant difference between inorganic or combined organic) and inorganic sources. Rice registered 9-21 % increase in grain yield when mustard crop residue or green manure wasapplied over the control, The organic materials applied alone or in combination with inorganic fertilizer had greater residual fertility in terms of increase in organic carbon content from 0.36 to as high as 0.61 % and the available N,P and K nutrients in 2 years cropping cycle.